2009
DOI: 10.1371/journal.ppat.1000580
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Evolution of Mycobacterium ulcerans Revealed by Next-Generation Sequencing

Abstract: Mycobacterium ulcerans is the causative agent of Buruli ulcer, the third most common mycobacterial disease after tuberculosis and leprosy. It is an emerging infectious disease that afflicts mainly children and youths in West Africa. Little is known about the evolution and transmission mode of M. ulcerans, partially due to the lack of known genetic polymorphisms among isolates, limiting the application of genetic epidemiology. To systematically profile single nucleotide polymorphisms (SNPs), we sequenced the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 76 publications
0
64
0
Order By: Relevance
“…Furthermore, given the comprehensive nature of full-genome data, sequences could also serve in large-scale microepidemiological studies that are focused on the elucidation of transmission pathways and relevant reservoirs of M. ulcerans. Indeed, different studies of mycobacterial genomics (18,49,56) have already shown that, at the whole-genome level, substantial genetic variation exists in African M. ulcerans, which can be exploited for phylogenetically robust strain classification. In order to capture as much diversity as possible and to minimize phylogenetic discovery bias (57) in such impending large sequencing endeavors, it will be desirable to select representative types from all the central and radial ISE-SNP types defined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the comprehensive nature of full-genome data, sequences could also serve in large-scale microepidemiological studies that are focused on the elucidation of transmission pathways and relevant reservoirs of M. ulcerans. Indeed, different studies of mycobacterial genomics (18,49,56) have already shown that, at the whole-genome level, substantial genetic variation exists in African M. ulcerans, which can be exploited for phylogenetically robust strain classification. In order to capture as much diversity as possible and to minimize phylogenetic discovery bias (57) in such impending large sequencing endeavors, it will be desirable to select representative types from all the central and radial ISE-SNP types defined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, WGS might perhaps be used to develop new epidemiological tools, identifying novel hallmarks of mycobacterial variability, rather than as a genotyping method per se. To exemplify this, WGS allowed the mapping of several SNP loci in M. ulcerans isolates, some of which further served as the templates for the development of a novel epidemiological differentiation pattern for this species (429). It also allowed the typing of several SNPs in M. leprae (430).…”
Section: Evaluation Of the Methodsmentioning
confidence: 99%
“…Genetic analyses indicate that M. ulcerans has diverged from the ubiquitous waterborne organism Mycobacterium marinum 19 perhaps around a million years ago. 20 While M. marinum usually infects fish and frogs and only occasionally causes granulomatous skin lesions in humans, 21 emergence of the …”
Section: Genomic Diversity Ecology and Virulence Of M Ulceransmentioning
confidence: 99%